Sikap Indonesia dalam Menghadapi Kejahatan Lintas Negara: Illegal Logging di Kalbar dan Kaltim - Irewati, Awani (Pusat Penelitian Politik, 2005)
In Indonesia, illegal logging is a massive problem that never ending. It is the problem that has resulted in demoralizing the rule of law and substantial revenues to the state. It is the cause of forest crimes, and has serious economic and social implications to the poor societies in the border. Therefore, the activites of illegal logging and illegal border trade in the Indonesia-Malaysia border have to be eradicated as soon as possible. In responding the problem, the two actors (govemment and non govemment) have to build cooperation in coping with this problem. Beside that, the govemment has to be able to take personal approach to the Malaysian govemment in dealing with this problem. This paper presents the mapping of illegal logging in the Kalbar, Kaltim - Sarawak, Sabah border lines, and answer the question of what responses the govemment and non govemment take in that problem.